Greenland 2 : migration [videorecording (DVD)] - Buckley, David, 1976- (Lionsgate, 2026)
"In the aftermath of a comet strike that devastates most of the earth, Greenland 2: Migration follows devoted family man John Garrity and his wife and son after they're forced to leave the safety of their bunker in Greenland to search for a new home in a shattered world. John leads the family on a dangerous journey, guided by his burning hope in a rumored safe haven. It's a journey against the odds that will test the family's deepest sense of love, sacrifice, and instinct to survive."--